Policy Strategy for the Alleviation of Out-of-School Children in Magelang Regency - Aria, Aria; Khozin, Khozin (Universitas Pahlawan Tuanku Tambusai, 2025)
The phenomenon of out-of-school children (ATS) in Magelang Regency is a serious problem that has an impact on individual and socio-economic development in the region. Although the national education participation rate is increasing, there are still gaps that cause thousands of children to drop out of school, mainly due to economic, socio-cultural, and geographical factors. This study aims to analyze local government policy strategies in alleviating ATS and identify the obstacles faced. The research method used is qualitative descriptive with data collection techniques through observation, interviews, and documentation. The results of the study show that the